2022
DOI: 10.1039/d1gc04240h
|View full text |Cite
|
Sign up to set email alerts
|

Supported Pd–Au bimetallic nanoparticles as an efficient catalyst for the hydrodeoxygenation of vanillin with formic acid at room temperature

Abstract: Hydrodeoxygenation (HDO) upgrade of biomass usually need high temperature or high pressure of H2. Herein, a g-C3N4 supported PdAu bimetallic nanoparticles was reported as the efficient catalyst for the HDO...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The synergistic effect between Ru−Pt and the high-valence Pt facilitated the adsorption and activation of methane, which made the catalyst exhibit higher activity and stability. Wu 23 et al have developed a loaded PdAu/g-C 3 N 4 catalyst. Due to the electronic effect between Pd−Au and the metal−support interaction, this catalyst exhibited good catalytic activity and stability in catalyzing the hydrodeoxygenation reaction of vanillin to formic acid at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic effect between Ru−Pt and the high-valence Pt facilitated the adsorption and activation of methane, which made the catalyst exhibit higher activity and stability. Wu 23 et al have developed a loaded PdAu/g-C 3 N 4 catalyst. Due to the electronic effect between Pd−Au and the metal−support interaction, this catalyst exhibited good catalytic activity and stability in catalyzing the hydrodeoxygenation reaction of vanillin to formic acid at room temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The synergistic effect between Ru–Pt and the high-valence Pt facilitated the adsorption and activation of methane, which made the catalyst exhibit higher activity and stability. Wu et al. have developed a loaded PdAu/g-C 3 N 4 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Such oxygenates are of low value owing to their instability and low calorific values. [ 5 , 6 ] To obtain high‐value chemicals and fuels, bio‐oils must undergo further treatment, such as hydrogenation or hydrodeoxygenation (HDO), which are effective methods for reducing the oxygen content and promoting conversion into more stable alcohols and hydrocarbons. [ 7 , 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…So far, various transition metal catalysts such as Pd, Co, , Cu, , and Ni , have been widely employed for efficient hydrogenation of vanillin to produce MMP. For example, Cai and his co-workers prepared g-C 3 N 4 -supported Pd–Au bimetallic catalysts for the HDO of vanillin and achieved 100% MMP yield at room temperature . Zhang et al reported that the catalyst Co/N-C-600 exhibited a vanillin conversion of 99% and MMP yield of 98.6% at 150 °C and 20 bar H 2 pressure for 10 h .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cai and his co-workers prepared g-C 3 N 4 -supported Pd−Au bimetallic catalysts for the HDO of vanillin and achieved 100% MMP yield at room temperature. 18 Zhang et al reported that the catalyst Co/N-C-600 exhibited a vanillin conversion of 99% and MMP yield of 98.6% at 150 °C and 20 bar H 2 pressure for 10 h. 16 Li et al synthesized a Nisupported ZrP catalyst for obtaining 97.25% vanillin conversion with a MMP yield of 88.39% under the conditions of 220 °C and 0.5 MPa H 2 for 0.5 h. 19 However, the intermediate HMP is also an important raw chemical for the synthesis of many functional materials such as renewable epoxy thermosets, polymers, and medicines. 20−24 The abovementioned progresses show that most of the reported catalysts are based on MMP as the terminal product instead of the intermediate HMP.…”
Section: ■ Introductionmentioning
confidence: 99%